Preparation and Ultrasonic Imaging Investigation of Perfluoropentane-Filled Polylactic Acid Nanobubbles As a Novel Targeted Ultrasound Contrast Agent - Xiao, Ruolei; Zhao, Zhiwei; Chen, Jiajuan; He, Liu; Wang, Huili; Huang, Lingping; Luo, Binhua (Frontiers in Materials, 2020)
In the study reported here, polylactic acid (PLLA) polymer was synthesized using stannous octoate (Sn(Oct)2) and N-(t-butoxycarbonyl) ethanolamine (EABoc) as the catalyst and the initiator, respectively. The selected PLLA polymer with proper molecular weight was used to prepare nanobubbles encapsulating with liquid perfluoropentane. Then, lactoferrin (Lf), which has a good affinity with tumor cells, was conjugated to PLLA nanobubbles. The resulting Lf–PLLA nanobubbles were examined from the perspective of appearance, size, zeta potential, and stability in vitro. The average hydrodynamic diameter of the Lf–PLLA nanobubbles was 315.3 ± 4.2 nm, the polydispersity index (PDI) was 0.153 ± 0.020, and the zeta potential was around −11.3 ± 0.2 mV. Under the transmission electron microscope (TEM), Lf–PLLA nanobubbles were highly dispersed and had a spherical shape with a distinct capsule structure. The Lf–PLLA nanobubbles also showed little cytotoxicity and low hemolysis rate and exhibited good stability in vitro. The enhanced ultrasound imaging ability of Lf–PLLA nanobubbles was detected by an ultrasound imaging system. The results of ultrasound studies in vitro showed that the liquid perfluoropentane underwent phase transition under ultrasonic treatment, which proved the Lf–PLLA nanobubbles could enhance the ability of ultrasonic imaging. The studies of ultrasonic imaging in nude mice bearing subcutaneous tumors showed that the ability of enhanced ultrasonic images was apparent after injection of Lf–PLLA nanobubbles. Acoustic behavior in vitro and in vivo showed that the Lf–PLLA nanobubbles were characterized by strong, stabilized, and the ability of tumor-enhanced ultrasound imaging. Thus, the Lf–PLLA nanobubbles are an effective ultrasound contrast agent for contrast-enhanced imaging.